Traité de négociation collective - Bourque, Reynald (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "Traité de négociation collective," by Gérard Hébert.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z